STRATEGI PENGEMBANGAN PRODUK UNGGULAN DAERAH BERBASIS KLASTER DI KOTA MALANG - Niskha Sandriana; Abdul Hakim; Choirul Saleh (REFORMASI, 2015)
The purpose of this research was to identify superior products based on SME’s clusters in Malang and select the priority strategy to develop SME’s cluster based on potential, capabilities and constraints. This research was conducted with a mixed research methods (mixed methods). Quantitative methods were used to determine the criteria for superior product Malang with the Cochran Q test method, determine the superior product based on clusters in Malang with Analytical Hierarchy Process (AHP), and determine the priority of the development SME’s cluster strategy with SWOT analysis method. Qualitative method was used to identify the internal and external factors which influences on the development of SME’s cluster. The results showed that the criteria were used to determine a superior product, such as (1) the uniqueness of the product/as regional trade mark; (2) contribution to the regional economy; (3) market; (4) the input conditions (availability of infrastructure, human resources, technology, capital); (5) partnerships; (6) policy and institutional support; (7) the impact on the environment; (8) the level of competitiveness. Identification Superior product based on clusters in Malang with Analythical Hierarchy Process (AHP) method showed that superior product of Malang is tempe and tempe chips from the Sanan cluster. It can be concluded that the chosen strategy is SO strategy, the strategy which use strength to take advantage of opportunities or strategies that support aggressive growth policy (Growth Oriented Strategy).